Economic, social, and environmental assessment of farming Nile tilapia in net-cages in a reservoir in hot semi-arid region during an extended drought event - Henry-Silva, Gustavo Gonzaga; da Silva Cacho, Júlio César; Moura, Rodrigo Sávio Teixeira; Flickinger, Dallas Lee; Valenti, Wagner C. [UNESP] (Springer Nature, 2022)
Water reservoirs have been constructed in hot semi-arid regions, which may be used to produce fish. The present study described major features of the economic, social, and environmental characteristics of a net-cage Nile tilapia production system, stocked with 100 and 120 fish/m3, implemented in a reservoir in the hot semi-arid region of Brazil during an extended drought event. The production cycle was reduced from 6-8 to 4 months because of the lack of water in the reservoir. This resulted in the harvest of small fish weighting ~300–350 g that reached a low value in the market. As a consequence, indicators of financial feasibility showed low values, which were not attractive for entrepreneurs. Nevertheless, for both stocking densities, the monthly income was about US$ 1,500.00, which is 5-fold the minimum wage in the region. In general, the activity has a positive social impact, despite the low contribution to development of the local economy and food security because most supply came from outside and fish were sold to distant regions. Various age and ethnic groups were represented among the employees, but the enterprise was operated only by men. Phosphorus accumulations in the reservoir were 2.1 and 2.0 kg/t of fish produced and particulate material accumulations of 110 and 100 kg/t of fish production for 125 fish/m3 and 100 fish/m3, respectively. The study indicated that the Nile tilapia culture in hot semi-arid region is strongly affected by long drought events and adaptations in the planning and management should be done when implementing the systems. However, it seems that the activity has some resilience to still provide food, generate wealth, and promote social development for local population with low environmental impact.
Keywords: Aquaculture; Environmental friendliness; Environmental impact; Fish farming; Indicators of sustainability; Oreochromis niloticus